(3JfejI YVdjI ai (B60 (3ObjbIs - (3gjcd, NGdOs ([(3O(B. (3es (3O(B. (3f(B. ]s, 2007)
(3GdcJGH jJfGhd CgejI GdQjGVI ce jhVM cjajI JbhjI GdLSe hGdYVdGJ hGdeMGaXI Ydi GdUMI hGddjGbI hEfbGU GdhRf ef NdGd (B60 (3ObjbI jhejGs
(3GdeMJhjGJ (B: (3CSeGA GdYVdGJ(B--(3dG JMQe faSc ef ahGFO eeGQSI GdQjGVI(B--(3gd (B60 (3ObjbI Jcai? (B--(3JfejI YVdjI ai (B60 (3ObjbI(B--(3GdJOQjH GdefJXe heTcdI GdhbJ(B--(3fUGFM gGeI(B--(3JMPjQs
(3jTJed Ydi JYQja ehLR HGdeDdas
Hurg
5 14
Keywords: (3GdCdYGH GdQjGVjIs; (3GdJOQjH GdQjGVis; (3GdJQHjI GdHOfjIs; (3GdJeQjfGJ GdQjGVjIs; (3GdQjGVI GdHOfjIs -- (3GdLhGfH GdaSjhdhLjIs; (3GdYVdGJs; (3GddjGbI GdHOfjIs